Current Update Waste to Energy in Developing Country; A Review and Bibliometric Analysis - Muis, Ramdiana; Anggraini, Nani; Radde, Hasniar Ambo; Rachman, Indriyani; Matsumoto, Toru (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
The concept of processing waste into energy has developed in the last few decades, especially in developing countries. This paper reviews a bibliometric overview of the waste-to-energy literature and related analyzes in developing countries in the last 10 years. The research method used is quantitative with bibliometric analysis on the Scopus database. Based on this method, the number of articles analyzed was 1,880 articles in the form of journals, conference papers, and scientific reviews. There are four stages of analysis, namely determining the source title, keywords, country, and selection literature. Data analysis using a bibliometric approach found 116 articles related to Waste-to-Energy Incineration in developing countries. This study uses VOSviewer software version 1.6.19 for data complexity. The results of this study indicate that the Waste to Energy was divided into five clusters with 56 keywords. The most powerful topics related to this Waste-to-Energy are Municipal Solid Waste and Technology. Research on related waste into energy has increased in developing countries since 2004. This study found keywords such as biofuel and electricity, indicating the current trends in Waste to Energy research in the visualization of research trend mapping.